2020
DOI: 10.1002/micr.30681
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of lower lip defects with free super‐thin anterolateral thigh flap

Abstract: Background Lower lip is a vital organ with important functions as well as aesthetic importance. It is critical to provide an aesthetically appealing lower facial subunit with maintenance of understandable speech and oral competence. Achieving these targets is very difficult especially in total lower lip defects. This report presents a technique using super‐thin anterolateral thigh (ALT) flaps with fascia graft for reconstruction of large, complex oral sphincter defects. Patients and methods Six patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
3
26
0
1
Order By: Relevance
“…However, the conventional ALT flap is often too bulky for resurfacing face defects, so it often needs to be performed a secondary debulking procedure. Moreover, the disadvantages of the free ALT are that skin color and texture are not similar to facial skin, and there is a high incidence of hair presence, especially in male patients [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the conventional ALT flap is often too bulky for resurfacing face defects, so it often needs to be performed a secondary debulking procedure. Moreover, the disadvantages of the free ALT are that skin color and texture are not similar to facial skin, and there is a high incidence of hair presence, especially in male patients [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the PAP free flap from the posteromedial thigh as a secondary donor site instead others free flaps, due to sev- Some of these traditional flaps, as the ALT or the SCIP, offer the advantage of excessive bulkiness avoidance, as they can be easily thinned intraoperatively with no need for secondary revisions, eventually (Bali et al, 2021;Hassan et al, 2020;Lee et al, 2017). Nevertheless, when compared to the ALT flap, the skin at the posteromedial thigh in the PAP flap has more laxity and this allows for primary donor site closure in most instances (Ciudad et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This flap is very versatile and can be trimmed and defatted to suit any type of defect. 5,[10][11][12] The FL can be used as an anchoring structure, similar to the PL tendon previously described. If this flap is not available, the second option is the PAP flap.…”
Section: Table 5 Algorithm For Extensive Lower Lip Defect Reconstructionmentioning
confidence: 99%
“…Composite anterolateral thigh (ALT) free flap and FL offer a good alternative, significantly reducing donor site morbidity. [10][11][12] Various authors have reported successful functional outcomes using free functioning muscle transfers. [13][14][15] In cases of combined lower lip-mandible defects, some authors advocate the use of a double free flap transfer, 16,17 whereas others use free fibula 18 or scapular flaps 19 with extended skin paddles.…”
mentioning
confidence: 99%